Role of Presidential Initiative on Aids Strategy for Communication to Youth in Influencing the Sexual Behaviour of Pupils in Kamwezi Sub-County. - Orikiriza, Jescah (Kabale University, 2024)
This study examined the impact of the Presidential Initiative on AIDS Strategy for Communication to Youth (PIASCY) on the sexual behavior of students in Kamwezi Sub-County, Uganda. Amid ongoing challenges of HIV/AIDS among young people, PIASCY seeks to raise awareness and encourage safe sexual practices through strategic communication efforts. The research evaluates the initiative’s outreach and effectiveness, shedding light on its resonance with local youth and its potential to shape their sexual behaviors. Using a mixed-methods approach, the study explores shifts in knowledge, attitudes, and practices regarding HIV/AIDS prevention among students exposed to PIASCY campaigns. Initial findings show a significant increase in awareness and more favorable attitudes towards safe sexual practices. However, the study also identifies ongoing issues with misconceptions and stigma, indicating that while PIASCY has made progress, there is still a need for ongoing education and engagement. Furthermore, the research highlights critical factors influencing the acceptance and implementation of PIASCY initiatives within Kamwezi Sub-County’s schools and communities. These factors cultural beliefs, peer influence, and resource availability significantly impact the campaign's effectiveness. Understanding these elements is vital for designing future interventions to improve sexual health outcomes for the youth in this area.